Vocial Assistant in Virtual - Singh, Suraj; Dutta, Ritushree; Chaudhary, Shiwani; Kumar, Hitesh (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2023)
Everything in the twenty-first century is automated, including the appliances we use every day like washing machines, dishwashers, refrigerators, bus doors, air conditioning systems, etc. The current study suggests a more modern idea for voice-controlled devices that can recognise a user's voice, process a request, and assign the time and date of an appointment based on that request with specifics like the person's name, the date, the time, and other pertinent information.We must create devices with built-in voice recognition that can distinguish between human voices even in congested environments using the speech as the only medium of communication. Through the device's microphone, the device will record audio, process the human's request, and respond to the human with the necessary information. For instance, if you ask the device to change your computer's wallpaper, it will do so by downloading a new wallpaper from a website and applying it to your computer. Additionally, it can automatically propose less-congested routes and assist you through the traffic between source and destination.